Modeling wind turbine blades by geometrically-exact beam and shell elements: A comparative approach. (1st February 2019) - Faccio Júnior, Celso Jaco; Cardozo, Ana Carolina Pegoraro; Monteiro Júnior, Valdemar; Gay Neto, Alfredo
Highlights: A geometrically-exact constitutive matrix for arbitrary beam axis is presented. Statics and dynamics of wind turbine blades are studied by beam and shell models. Local buckling close to blades' trailing edge was captured by shell models. Beam models could capture well the overall geometric nonlinearities. Beam models could well-predict overall stiffness for cases with some local buckling. Abstract: Novel designs of wind turbine blades may lead to very flexible structures experiencing large deformation not only in extreme events but also on operational conditions. In this context, this work aims to compare two geometrically nonlinear structural modeling approaches that handle large deformation of blade structures: 3D geometrically-exact beam and shell finite element models. Specifically, the focus is on studying the accuracy limits of the beam model when compared to the shell model in scenarios of large deformations. Regarding the beam model, due to geometric complexity of typical cross-sections of wind turbine blades, a theory is adopted that allows for the creation of arbitrary multicellular cross-sections. Two simplified blade geometries are considered, and comparisons between the models are made in statics and dynamics. Results showed that the beam and shell models present very similar global behavior. Locally, however, extreme load cases led shell models to show local buckling phenomena close to the trailing edge, which may play a role in novel HAWT designs.